Hubungan Antara Iman dan Perbuatan: Tinjauan Dari Injil-Injil Sinoptik dan Kisah Para Rasul - Priyono, Joko (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
This study aims to conduct an in-depth analysis of the relationship between faith and actions in the texts of the Synoptic Gospels and the Acts of the Apostles. Employing a qualitative descriptive approach, this research integrates theological and psychological perspectives to explore how faith influences an individual's actions in the context of Christian life. The findings of the study indicate that genuine faith manifests in actions consistent with a transformed heart through repentance, as well as the importance of voluntary actions as responses to the power and grace of God. Salvation is viewed as the outcome of voluntary actions and individual awareness to surrender oneself to Christ. This study not only contributes theoretically to the understanding of Christian theology but also provides practical guidance for individuals seeking to deepen their faith relationship with God through everyday actions. It is hoped that this research will open up new insights and inspire a deeper understanding of the essential relationship between faith and deeds in the context of Christian life.